1998
DOI: 10.1007/s004320050214
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipoperoxide levels and antioxidant system in colorectal cancer

Abstract: In this study, lipid peroxide and glutathione (GSH) levels, GSH peroxidase, GSH S-transferase, superoxide dismutase, gamma-glutamylcysteine synthetase and gamma-glutamyl transpeptidase activities were investigated in tumorous and nontumorous colorectal tissues obtained from ten patients diagnosed with colon and rectum cancer. Histopathological evaluations, including type, stage, necrosis and lymphocyte infiltration, were also performed for each patient. According to the results, lipid peroxide and GSH levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
7
26
0
1
Order By: Relevance
“…The GST levels in tumor tissue of colorectal cancer were similar to the GST levels in the normal colorectal tissue of subjects with colorectal cancer (17). No significant difference in activity of GST was observed in human breast cancer tumor cell line and Adriamycin resistant cell line.…”
Section: The Mean + Sd Values Of Glutathione (Gsh) Malondlaldehyde (supporting
confidence: 59%
See 1 more Smart Citation
“…The GST levels in tumor tissue of colorectal cancer were similar to the GST levels in the normal colorectal tissue of subjects with colorectal cancer (17). No significant difference in activity of GST was observed in human breast cancer tumor cell line and Adriamycin resistant cell line.…”
Section: The Mean + Sd Values Of Glutathione (Gsh) Malondlaldehyde (supporting
confidence: 59%
“…However MDA levels have been reported to be higher in patients with malignant breast tumor (15, *p < 0.0001 compared to controls **p = 0.05 compared to controls. ns -not significant when compared to controls (p > 0.05) NS -not significant when compared to pre treatment (p 9 0.05) 16), colorectal cancer tissue (17) and in erythrocytes of rats with hepatoma (9).…”
Section: Resultsmentioning
confidence: 95%
“…An increase in lipid peroxidation, both in blood and cancerous tissue samples, has been previously reported in primary CRC patients [39][40][41]. In particular, Skrzydlewska et al [41] found a steady increase of the lipid peroxide adduct MDA in malignant tissue of stages II-IV and a sustained increase in 4-HNE.…”
Section: Oxidation State Of Crc Along Stages and Its Relationship To mentioning
confidence: 80%
“…There is, however, known to be a large geographical difference in the incidence of colorectal cancer with the highest number of cases in western countries such as Europe and the USA, whilst studies in migrant populations have shown that colorectal cancer incidence increases upon changing to a western diet [4][5][6], although changes in other lifestyle factors such as physical activity levels have also been implicated. Dietary fat, lipid peroxidation (LPO) and arachidonic acid metabolism have all been linked, amongst other factors, to colorectal carcinogenesis in a number of studies [7][8][9]. LPO is initiated by the attack of free-radicals on membrane lipids leading to reactive products that may be linked to tumour initiation.…”
Section: Introductionmentioning
confidence: 99%